The Prevalence of Vertebral Fractures Is Associated With Reduced Hip Bone Density and Inferior Peripheral Appendicular Volumetric Bone Density and Structure in Older Women. (15th November 2017) - Johansson, Lisa; Sundh, Daniel; Zoulakis, Michael; Rudäng, Robert; Darelid, Anna; Brisby, Helena; Nilsson, Anna G; Mellström, Dan; Lorentzon, Mattias
ABSTRACT: Vertebral fractures (VFs) are among the most severe and prevalent osteoporotic fractures. Their association with bone microstructure have been investigated in several retrospective case‐control studies with spine radiography for diagnosis of VF. The aim of this population‐based cross‐sectional study of 1027 women aged 75 to 80 years was to investigate if prevalent VF, identified by vertebral fracture assessment (VFA) by dual‐energy X‐ray absorptiometry (DXA), was associated with appendicular volumetric bone density, structure, and bone material strength index (BMSi), independently of hip areal bone mineral density (aBMD). aBMD was measured using DXA (Discovery; Hologic); BMSi with microindentation (Osteoprobe); and bone geometry, volumetric BMD, and microstructure with high‐resolution peripheral quantitative computed tomography (HRpQCT) (XtremeCT; Scanco Medical AG). aBMD was lower (spine 3.2%, total hip [TH] 3.8%) at all sites in women with VF, but tibia BMSi did not differ significantly compared to women without VF. In multivariable adjusted logistic regression models, radius trabecular bone volume fraction and tibia cortical area (odds ratio [OR] 1.26; 95% confidence interval [CI], [1.06 to 1.49]; and OR 1.27 [95% CI, 1.08 to 1.49], respectively) were associated with VF prevalence, whereas BMSi and cortical porosity were not. The risk of having one, two, or more than two VFs was increased 1.27 (95% CI, 1.04 to 1.54), 1.83 (95% CI, 1.28 to 2.61), and 1.78 (95% CI, 1.03 to 3.09) times, respectively, for each SD decrease in TH aBMD. When including either cortical area, trabecular bone volume fraction or TBS in the model together with TH aBMD and covariates, only TH aBMD remained independently associated with presence of any VF. In conclusion, TH aBMD was consistently associated with prevalent VFA‐verified VF, whereas neither trabecular bone volume fraction, cortical area, cortical porosity, nor BMSi were independently associated with VF in older women. © 2017 American Society for Bone and Mineral Research.